Peran Guru Dalam Mengatasi Perilaku Bullying Siswa di SMA Negeri 1 Kapuas Timur, Desa Anjir Serapat, Kecamatan Kapuas Timur, Kabupaten Kapuas - Riza Rivaldi; Syahlan Mattiro; Reski P (PADARINGAN (Jurnal Pendidikan Sosiologi Antropologi), 2024)
The teacher's role is to create a series of interrelated behaviors carried out in a particular situation that are related to the progress of behavior change and student development which is the goal. In overcoming bullying behavior carried out by students at school, teachers play a very important role so that students do not carry out bullying at school. This research aims to determine (1) teachers' efforts to overcome student bullying behavior at SMA Negeri 1 Kapuas Timur. (2) the obstacles faced by teachers in overcoming student bullying behavior at SMA Negeri 1 Kapuas Timur. The method used in this research is qualitative method. Data sources were selected using purposive sampling. The data collection techniques used were observation, interviews and documentation. The data analysis techniques used in this research are data reduction, data presentation, and drawing conclusions. Testing the validity of the data carried out included: triangulation of sources, techniques and time. This research resulted in: (1) Teachers' efforts to overcome bullying behavior using three methods of socialization, namely through socialization in the classroom, secondly, socialization to stop bullying through poster media, and finally, socialization through advice from the ceremony supervisor every Monday. (2) The obstacles faced by teachers in overcoming student bullying behavior include three factors, namely the family environment, friendship or peer environment, and introverted attitudes. Second, the friendship environment. Third, introverted nature or personality. Based on the research results, it is recommended that teachers provide complaint forms regarding bullying and controlling every activity carried out by students. Students are advised to make a complaint report about bullying to the counseling counseling room